Morphogenesis of neurohypophysis during prenatal development in buffalo - SETHI, R S; SINGH, OPINDER (The Indian Journal of Animal Sciences, 2011)
The study was conducted on 19 buffalo foetuses ranging from 30 mm to 630 mm crown rump length (CRL). The tubular infundibulum evaginated from the diencephalon at 35 mm CRL. It was in close contact with the caudal wall of the Rathkeâ€™s pouch and was lined with tall ependymal cells. At 43 mm CRL infundibulum became perpendicular to long axis of the foetus and showed cellular proliferation and foldings which resulted in the differentiation of neurohypophysis at 60 mm CRL. The lumen of the infundibulum disappeared at 80 mm CRL stage. The pars distalis, pars intermedia and hypophyseal cleft were seen enwrapping the neurohypophysis at 120 mm CRL and onward stages. Â